Lace and Knitting in Boiko`S Clothing Decor: Ethnic Local and Art Features - Козакевич, О. Р. (Art and Design, 2021)
Local and artistic features of Boiko`s region traditional clothing décor are studied. The attention is given to lace and knit decor, which gave the clothing components a unique and often was the artistic accent in Boiko`s clothing complexes. The methodological basis of the study is the principle of systematic approach and comprehensive research. The comparative-historical and typological methods were used for the study research subject. The analysis of lace and knit décor was done using the art study method. The main typological groups and items` types formed under the influence of ethno-cultural and historical factors were determined in the Boiko`s region based on artifacts from museum collections, field studios and scientific sources. The décor manufacturing textile techniques and technological methods are outlined, with pointed of common and distinctive features in comparison with folk clothing of the Carpathian region`s other ethnographic groups. Artistic and stylistic characteristics of knitting and lace are analyzed, taking into account the interplay of neighboring ethnicities cultures and border features. It is studied out that the lace décor was mostly common in female headwear, the waist wear and shirts. Sprang, lace, crocheting weaving techniques as well as other technological methods were used in the manufacturing lace adornments. Knitting, crocheting and weaving “on the laba” were used for gloves, “narakvytsias”, and socks-stockings manufacturing. In folk clothing Boikos applied weaving belts which were made in technique “on the wall”. This kind of belts also were used in Hutsul`s region – mainly on the Hutsul-Pokuttia border and were not common in Boikos. According to the artistic and stylistic features, it is possible to single out female coifs with lace bottoms, openwork ornaments on female shirts of Transcarpathian Boiko`s region, decoration low edges of aprons (“zapaskas”) with fringes using macramé. However, the ethno-local and artistic characteristic of lace and knitting within single centers were differed in their unique features. Scientific novelty consists in the introduction into the scientific circulation of materials about Boiko`s folk clothing. The focus is on the lace and knit décor that reveals the artistic diversity of Boiko`s region clothing art. The study allows expanding the knowledge of Boiko`s traditional garment and textile production, in particular, about the centers of manufacturing some types of clothing with openwork and knitting. This contributes to use the receives information in the further study of Boiko`s region traditional clothing.